IMITATION MODELING FOR ASSESSING THE LEVEL OF BALANCED DEBT OF THE BANKING SYSTEM CLIENTS IN RUSSIA - Denis V. Domashchenko (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses methodological issues of designing the imitation model for identifying the level of balanced debt of Russian banks' borrowers. The imitation model advanced by the author gives an opportunity to take into account the impact of uncertain factors of the environment on economy and banking business and to find disproportions in the banking system to take steps for their elimination. Calculations made by the author with the help of the said model show growing processes of deleverage in the private sector. At the same time the balanced level of client debt to banks can reduce by 6-10 trillion rubles without interest rate and foreign currency re-estimation in conditions of oil prices going lower than 40USD per barrel.